Evaluation of the Effectiveness of Legal Protection for Consumers for Unused Electricity Bills in Batam - Zulfi, Natasya Artameivia; Seroja, Triana Dwi; Sudirman, Lu (LEGAL BRIEF, 2025)
Electricity is a primary necessity in today's world, and it has an impact on a country's economic growth. PT PLN Batam, as a subsidiary of PT PLN (Persero), is not only a provider of electricity but also must prioritize the quality of service to consumers. However, in practice, there are consumers who experience an increase in electricity bills compared to the previous month, and they do not receive a clear and proper explanation from PT PLN Batam regarding their electricity usage. The purpose of this research is to analyze the form of legal protection for consumers against electricity bills without usage in Batam and to evaluate the effectiveness of legal protection for consumers against such bills in Batam. The research method used in this study is empirical legal research, as it is conducted through field studies by observing the implementation of applicable regulations in the community. The results of this research show that legal protection for consumers against electricity bills without usage in Batam is still weak due to the low legal awareness from both PT PLN Batam and consumers, as well as the lack of clarity in the Electricity Law regarding the steps consumers can take. The effectiveness of legal protection is also hampered by the use of difficult-to-understand language in SPJBTL, the low legal awareness of the public, and the lack of legal literacy regarding consumer rights and obligations. This leads to difficulties for consumers in resolving issues related to electricity bills that do not match their actual usage